The Impact of Communal Clashes on Economic Development of Takum Local Government Area, Taraba state - Atiyaye, Dauda Mohammed; Kaku, Mohammed; Jijji, Mohammed Mohammed; Kele, Ali; Goni, Umar Mohammed (Kashere Journal of Politics and International Relations, 2025)
Communal clashes have become a persistent security challenge in Takum Local Government Area (LGA) of Taraba State, significantly affecting economic development. These conflicts, often driven by ethnic tensions, competition over land and water resources, political grievances, have disrupted key economic activities, particularly agriculture, trade, and investment. This study examines the extent to which communal violence impacts economic growth in Takum LGA, analysing its effects on productivity, market stability, infrastructure, and livelihoods. Using a qualitative method, the research dwelt on data gathered through surveys, interviews, and secondary sources. Findings indicate that frequent communal conflicts have led to displacement, loss of farmlands, business closures, and reduced investment confidence. The resulting insecurity has weakened local economies, discouraged infrastructural development, and exacerbated poverty levels. To address these challenges, the study advocates for sustainable peace-building initiatives, strengthened conflict resolution mechanisms, and improved security interventions. It recommends proactive government policies, enhanced inter-community dialogue, and targeted economic recovery programs to rebuild livelihoods and restore investor confidence. By fostering long-term stability, these measures can pave the way for sustainable economic growth in Takum LGA.